Cutting age and nutritional value of mulberry (Morus alba) foliage meal for pigs - Mireles, S.; Moreno, E.; Ruiz, M.; Samkol, Pok; Yaro, Y.; González, D.; Ly, J. (Cuban Journal of Agricultural Science, 2019)
Twelve plots of 15 m2 planted with an indeterminate variety of mulberry (Morus alba) with wide leaves underwent periodic cuts every 30, 60, 90 and 120 days to study, according to a random block design, the nutritional value of mulberry foliage meal by the technique of in vitro ileal (pepsin/pancreatin) and fecal digestibility. Cell wall content and N bound to that wall increased significantly (P = 0.004) with the cut age while the N content tended to decrease (P = 0.059). The ileal digestibility of organic matter and N decreased from 68.1 and 59.4 % to 44.2 and 30.0 % (P <0.05), respectively, in samples of 30 cutting days up to others of 120 days (P <0.01). Similarly, fecal digestibility of DM and organic matter went from 66.7 and 68.0 % to 45.3 and 51.0 % (P <0.01), respectively. Cutting age exerts a determining influence on the nutritional value of mulberry foliage meal provided to pigs, which worsens as cut frequency decreases. Keywords: tree forage, pigs, digestibility, yield, fiber